Measurement of the time-dependent CP asymmetries in B0s → J/ψK0S - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; et al. (Journal of high energy physics, 2015)
The first measurement of decay-time-dependent CP asymmetries in the decay B0s → J/ψK0S and an updated measurement of the ratio of branching fractions B(B0s → J/ψK0S)/B(B0 → J/ψK0S) are presented. The results are obtained using data corresponding to an integrated luminosity of 3.0 fb−1 of proton-proton collisions recorded with the LHCb detector at centre-of-mass energies of 7 and 8 TeV. The results on the CP asymmetries are A∆Γ(B0s → J/ψK0S) = 0.49 ±0.650.77stat±0.06syst, Cdir(B0s → J/ψK0S) = −0.28 ± 0.41(stat) ± 0.08(syst), Smix(B0s → J/ψK0S) = −0.08 ± 0.40(stat) ± 0.08(syst). The ratio B(B0s → J/ψK0S)/B(B0 → J/ψK0S) is measured to be 0.0431 ± 0.0017(stat) ± 0.0012(syst) ± 0.0025(fs/fd), where the last uncertainty is due to the knowledge of the B0s and B0 production fractions.